Liver in obesity. Issue 2 (February 1985) - Braillon, A; Capron, J P; Hervé, M A; Degott, C; Quenum, C
Abstract : We report on clinical, nutritional, and hepatic histological findings in 50 non-selected obese subjects (mean overweight +74%; range +21-138%). The pathogenesis of the liver damage was assessed with the help of multidimensional analysis of a number of clinical variables. According to the severity of the hepatic lesions, the patients have been ranged in five groups: O (normal liver) 10%; I (fatty liver) 48%; II (fatty hepatitis) 26%; III (fatty fibrosis) 8%; IV (fatty cirrhosis) 8%. The more severe changes (groups III and IV) were constantly associated with excessive alcohol intake. The multidimensional analysis was unable to find a relationship between obesity and the development of fibrosis and cirrhosis whereas it showed that: (a) there was a highly significant correlation between the daily ethanol intake and the degree of overweight, (b) severe fatty metamorphosis was significantly associated with the degree of overweight, the existence of diabetes mellitus, and the amount of alcohol and fat intake, (c) nutritional factors, in particular deficient protein intake, have only an accessory effect in the development of mild inflammation and fibrosis, (d) the consumption of potentially hepatotoxic drugs, very high in the obese (about five drugs per day) could have a role in the development of cirrhosis. In conclusion in our study, there was no evidence that obesity per se could result in severe liver damage.